Valence state of iron and molybdenum cations under conditions of anionic deficiency in Sr2FeMoO6–δ - Kalanda, Nikolay (2020)
The activation energy of oxygen diffusion in strontium ferromolybdate Sr2FeMoO6–δ was determined by the Merzhanov technique based on the temperature dependences of the oxygen desorption dynamics. It was found that the activation energy has a minimal value of 76.7 kJ/mol at δ = 0.005 and maximum value of 156.3 kJ/mol at δ = 0.06. It was suggested that, with an increase in the oxygen vacancies concentration, an interaction occurs between them and the nearest cations with the subsequent formation of associates of various types that are less mobile than the single anion vacancies. According to the Mössbauer spectroscopy data, it was established that the appearance of oxygen vacancies and their ordering contribute to the isomer shift, and some of the iron ions occupy the tetrahedral (or close to it) positions in the lattice. This indicates the formation of associates of oxygen vacancies. The results of XPS studies have shown that the increase in the concentration of oxygen vacancies results in a decrease of the Mo6+ and Fe2+ concentration. At the same time, the number of Mo5+ and Fe3+ cations increases due to the redistribution of the electron density, and molybdenum cations in a different valence state (Mo4+) appear.